2017
DOI: 10.1002/2016jd026222
|View full text |Cite
|
Sign up to set email alerts
|

Detecting shifts in tropical moisture imbalances with satellite‐derived isotope ratios in water vapor

Abstract: As global temperatures rise, regional differences in evaporation (E) and precipitation (P) are likely to become more disparate, causing the drier E‐dominated regions of the tropics to become drier and the wetter P‐dominated regions to become wetter. Models suggest that such intensification of the water cycle should already be taking place; however, quantitatively verifying these changes is complicated by inherent difficulties in measuring E and P with sufficient spatial coverage and resolution. This paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 67 publications
5
41
0
2
Order By: Relevance
“…Figures d, e, and S6 show the difference in water isotopes in vapor in TES satellite retrievals for composite ENSO events spanning 2004–2011 and compares changes in ω to observations of water isotope ratios and iCAM5‐simulated δ D V . These observations, though limited in time, suggest circulation changes with ENSO leave an isotopic fingerprint (Bailey et al, ) and that a decelerated Walker tends toward El Niño‐like conditions (in agreement with Vecchi & Soden, ). Further, Figures d and e show that δ D V estimated from TES satellite retrievals for El Niño versus La Niña are consistent with the models' future prediction of a shoaling W−E gradient in δ D V with mean warming.…”
Section: Discussion: Detecting Changes In the Walker Circulationsupporting
confidence: 69%
See 2 more Smart Citations
“…Figures d, e, and S6 show the difference in water isotopes in vapor in TES satellite retrievals for composite ENSO events spanning 2004–2011 and compares changes in ω to observations of water isotope ratios and iCAM5‐simulated δ D V . These observations, though limited in time, suggest circulation changes with ENSO leave an isotopic fingerprint (Bailey et al, ) and that a decelerated Walker tends toward El Niño‐like conditions (in agreement with Vecchi & Soden, ). Further, Figures d and e show that δ D V estimated from TES satellite retrievals for El Niño versus La Niña are consistent with the models' future prediction of a shoaling W−E gradient in δ D V with mean warming.…”
Section: Discussion: Detecting Changes In the Walker Circulationsupporting
confidence: 69%
“…Currently, available satellite missions measure δ D V in the atmospheric boundary layer, the free atmosphere, or total column; our study suggests that more accurate midtroposphere measurements (above ∼700 hPa) may be needed to detect changes in convective mass flux using water vapor isotope ratios. Recent work using TES observations across El Niño‐Southern Oscillation events show variations of 20–40‰ in δ D V suggesting that it is possible to distinguish between warmer and colder phases in the tropical Pacific and related circulation changes (Bailey et al, ). Figures d, e, and S6 show the difference in water isotopes in vapor in TES satellite retrievals for composite ENSO events spanning 2004–2011 and compares changes in ω to observations of water isotope ratios and iCAM5‐simulated δ D V .…”
Section: Discussion: Detecting Changes In the Walker Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This general result agrees with conventional interpretation of the joint distributions of tropical q ‐ δ D. The convention considers middle troposphere humidity as largely a product of large‐scale horizontal mixing. In regions of large‐scale convection, however, Rayleigh fractionation, moisture convergence, rainfall evaporation, and intensity are more dominant processes (Bailey et al, ; Lee et al, ; Moore et al, ). This finding, which highlights the transport characteristics of the δ D associated with the MJO, contrasts with the bulk analysis of Duan et al (), who showed that δ D has many similarities with relative humidity for the tropical mean.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, precipitation and ice cores in Alaska sometimes show stronger correlations between water isotope ratios and moisture source region than temperature (Fisher et al, 2004;Putman et al, 2017), and modern precipitation measurements in the tropical Pacific suggest that isotope ratios respond more sensitively to variations in the intensity and organization of convection regionally than to the amount of local precipitation (Conroy et al, 2016;Kurita, 2013;Kurita et al, 2009;Moerman et al, 2013). More recently, studies have shown correlations between isotope ratios and regional imbalances in E and P (Feng et al, 2009;Lee et al, 2007;Moore et al, 2014) or associated variations in atmospheric residence time and moisture transport (Aggarwal et al, 2012;Bailey et al, 2017;Putman et al, 2017). Nevertheless, to decipher changes in hydrologic balance from isotope ratios, a strong theoretical framework that can explain these correlations is necessary.…”
Section: 1029/2018gl078254mentioning
confidence: 99%